Enriching the Lagos Model of Student Teaching with Pedagogical Provisions from the Columbia Model (Universitas Negeri Semarang, 2021)
The achievements of teacher preparation models have been studied through the use of input-output models. While teacher education programmes are considered to be the input, student achievements are the output. Consequently, certain models have been found to be more effective and evaluated more than others. It is noted that of all the components that constitute teacher education programme, the student teaching has received less attention. This study evaluates the student teaching sub-components of the University of Lagos, Faculty of Education and the University of Columbia Teachers College, with a view to attempting an enrichment of the former with some of the best pedagogical provisions from the latter. With the use of an adopted instrument tagged Comprehensive School Reforms Classroom Observation System (CSRCOS) and other trainee records, the evaluation identifies strengths and weaknesses as well as best practices for enrichment purposes. Results reveal that there were disparities in Lagos teacher trainees’ scores by their Departments and over a period of three academic sessions. These disparities can be defined and explained by the mode and type of field experience that the student teachers were exposed to. The study underscores some of the Columbia pedagogical practices for systematic replication by the Lagos Model. Abstrak Capaian model persiapan guru sering dikaji menggunakan model input-output yang menempatkan pendidikan keguruan sebagai bagian dari input dan capaian belajar siswa bagian dari output. Beberapa model diketahui lebih efektif disbanding lainnya, hanya saja komponen program Pendidikan guru dan pengajaran oleh siswa tidak banyak memperoleh perhatian. Oleh karena itu, penelitian ini mengkaji praktik pengajaran siswa sebagai bagian dari program Fakultas Ilmu Pendidikan, Universitas Lagos dan Columbia Teachers College yang diatahkan untuk memperkaya praktik pengajaran dengan mengadopsi instrument Comprehensive School Reforms Classroom Observation System (CSRCOS) dan catatan pelatihan lainnya. Kajian dalam penelitian ini mengidentifikasi kekuatan dan kelemahan yang ada dengan tujuan memperkaya pengalaman mengajar siswa. Melalui penelitian ini diperoleh kesenjangan di program pelatihan guru di Lagos sesuai departemen masing-masing dalam kurun waktu tiga semester. Kesenjangan tersebut dikategorisasikan sesuai dengan mode dan tipe pengalaman lapangan siswa mengajar. Kajian ini menegaskan bahwa terdapat beberapa praktik baik pedagogic dari Columbia Teachers College yang direplikasi secara sistematis oleh model Lagos.